Hierarchical ZnO/Bi2O3 nanostructures : synthesis, characterization, and electron-beam modification - Ling, Bo (2012)
Two types of ZnO/Bi2O3 nanonecklace heterostructures were fabricated using the vapor-phase transport (VPT) method for the first time. These hierarchical structures were well characterized by X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), and transmission electron microscopy (TEM) with energy dispersive spectroscopy (EDS) attached. The growth mechanism of the novel structures were proposed based on these characterizations. Electron-beam irradiation was found to be a powerful and controllable tool in further tailoring such ZnO/Bi2O3 nanonecklace heterostructures. In addition, photoluminescence (PL) emission from the hierarchical nanostructures showed enhancement comparing to the pure Bi2O3 powder.